In silico study on inhibitability of flavonoidal derivatives against Helicobacter pylori and their pharmacological potentiality. Issue 4 (23rd May 2022) - Quy, Phan Tu; Du, Ly Nguyen Hai; Triet, Nguyen Thanh; Bui, Thanh Q.; Hai, Nguyen Thi Thanh; Thang, Le Quoc; Cuong, To Dao; Van Chen, Tran; Nhung, Nguyen Thi Ai
Abstract: Flavonoidal derivatives sinensetin (F1 ), isoorientin (F2 ), naringenin (F3 ), morin (F4 ), daidzein (F5 ) were experimentally demonstrated with effectiveness against Helicobacter pylori, thus speculated for their inhibitory effects towards structures of mucin‐5AC protein (UniProtKB‐P98088) and urease (PDB‐1E9Z), and subjected for in silico investigations. Their quantum properties were examined using density functional theory (DFT). The ligand‐protein inhibitability was evaluated using molecular docking simulation. Physicochemical properties were obtained from QSARIS‐based analysis in reference to Lipinski's rule of five. Pharmacokinetic parameters were assessed by ADMET‐based analysis. DFT calculations indicate that there are no abnormal bonding constraints observed. NBO analysis suggests F2 and F4 possessing favourable electric configurations for intermolecular inhibition. Regarding ligand‐P98088, the order for static inhibitability is F2‐P98088  > F4‐P98088  > F3‐P98088  > F5‐P98088  > F1‐P98088 . Regarding ligand‐1E9Z, the corresponding order follows: F2‐1E9Z  ≈ F4‐1E9Z  > F5‐1E9Z  > F3‐1E9Z  ≈ F1‐1E9Z . QSARIS‐based analysis reveals that all the candidates are highly bio‐compatible. ADMET‐based analysis specifies F2 as being safe and suitable for the use as orally administrated drugs. The results encourage further investigations for more in‐depth mechanisms and experimental validations, such as in vitro enzyme assays or clinical trials. Abstract :